Challenges and Opportunities in Private Extension Services for Shrimp Aquaculture in Andhra Pradesh, India - Deepthi, A.; Reddy, A. Devivaraprasad; Kumar, N.V. Sujath; Sudhakar, O. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Shrimp farming has emerged as a significant economic activity in Andhra Pradesh, India, driven by the region's favorable coastal geography and climatic conditions. This study investigates the role of private sector involvement in enhancing extension services for shrimp farmers in the state. Data were collected from 400 farmers across four major shrimp-cultivating districts through structured interviews. Findings revealed a positive farmer perception of private sector extension services and their availability across twelve key areas. However, fourteen constraints limiting the utilization of these services were identified. The study further underscores the dominant position of private companies in controlling shrimp farming inputs and services. Involving the private sector is crucial for the successful delivery of extension services that promote aquaculture development. These results provide insights into the potential and challenges of private sector-led extension in the shrimp aquaculture sector of Andhra Pradesh.